PENGARUH KEPEMIMPINAN, MOTIVASI DAN KOMPETENSI TERHADAP KINERJA PEGAWAI DINAS PENDIDIKAN DAN KEBUDAYAAN KABUPATEN KARANGANYAR - Mahanani, Fauziah Resma Runtun; Aji, Ambyah Atas (FAKULTAS EKONOMI DAN PSIKOLOGI UNWIDHA KLATEN, 2023)
In this research, the writer's goal was to determine the effect of the independent variables (Leadership, Motivation and Competence) on the dependent variable (Employee Performance) at the Karanganyar Regency Education and Culture Office. The hypothesis in this study is that leadership, motivation and competence have a significant effect on the performance of employees of the Karanganyar Regency Education and Culture Office both partially and simultaneously. The population in this study were 120 employees of the Karanganyar Regency Education and Culture Office. The sampling technique used is a simple random technique, with a total sample of 60 people. The data collection method used is a questionnaire and secondary data from literature studies. The data obtained has been tested for reliability and validity using validity and reliability tests. The method used in this study is Multiple Linear Regression analysis. Based on the results of multiple linear regression, it shows that all variables have a significant effect on employee performance. Simultaneously, the variables of leadership, motivation and competence have a significant effect on the performance of employees of the Education and Culture Office of Karanganyar Regency. Based on the results of the coefficient of determination, the variables of leadership, motivation and competence have an influence on employee performance the Education and Culture Office of Karanganyar Regency amounted to 41.7% while the remaining 58.3% was influenced by other factors